(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: To evaluate the frequency of anatomical variations in multidetector computed tomography of nasal cavities.Methods: This is a retrospective study of eighty-three computed tomography scans of patients presented to the outpatient department with sinonasal symptoms. The scans were reviewed for deviated nasal septum, nasal septal pneumatization, septal spur, paradoxical turbinate and concha bullosa.Results: The mean age is 33±16.9 years. The female and male ratio is 1:1.4. The most frequent variant is deviated nasal septum and the second common is the septal spur. The least common is the pneumatized nasal septum.Conclusion: Considering the variations in the anatomical structures, each and every nasal case should be proposed individually to computed tomography and studied carefully to avoid complications and increase the benefits of the patients.